Independent Risk Factors for Poor Outcome After Hip Arthroscopy. Issue 7 (21st July 2017) - Capogna, Brian; Hamula, Mathew; Begly, John; Wolfson, Theodore; Looze, Christopher; Ryan, Michael K.; Youm, Thomas
Objectives: Hip arthroscopy has been an increasingly used tool in the treatment of labral tears, chondral defects and ligamentum teres lesions and has demonstrated efficacy in returning patients to function and relieving their pain. Despite this, failures continue to occur. Our understanding of risk factors for failure or poor outcome continues to evolve as larger cohorts of patients are available for study. We sought to identify risk factors for poor outcome in our patient population. Methods: Prospectively collected data for all patients undergoing hip arthroscopy by a single fellowship-trained surgeon was obtained. All patients were indicated for hip arthroscopy based on standard pre-operative examination as well as routine and advanced imaging. Baseline demographic data regarding patient age, gender, BMI was collected. Patients without two year follow-up were excluded. Baseline pre-operative modified Harris Hip Scores (mHHS) were compared to mHHS at two-year follow-up. "Poor outcome" of initial hip arthroscopy was defined as any combination of: requiring a revision procedure or conversion to THA or mHHS below 70. Multivariate logistic regression was performed to identify independent risk factors for "poor outcome." Results: 258 patients met inclusion criteria. Mean age (SD) and body mass index (BMI) were 40.4 years (12.7 years) and 25.6 (4.7) respectively. 62.8% (162/258) of the sample was female. Mean preoperative baseline mHHS was 49.6 (12.5) and average mHHS at two year follow-up was 83.6 (15.6), resulting in a mean improvement of 34.1 (p<0.001). Baseline and 2 year differencess in mHHS by demographic be found in Figures 1, 2, 3, . Overall revision/THA conversion rate was 16.7% (43/258), while another 10.5% (27/258) of patients reported outcome scores <70, resulting in 27.31% (70/258) having poor outcomes. Independent risk factors for poor outcome were female gender (OR 1.79; p=0.03), obesity (OR 2.1; p=0.04), and pre-operative mHHS lower than 40 (OR 3.34, p<0.001). Conclusion: Our findings that female gender, obesity and poorer preoperative functional status increase the risk for failure of hip arthroscopy coincide and add to an increasing volume of literature examining risk factors for poor outcome after hip arthroscopy. These factors should be taken into consideration with operative indications as well as in counseling patients.